The Concept of Statehood and the Status of Taiwan - Davis, Michael C. (Columbia Journal of Asian Law, 1990)
As the twenty-first century dawns, Taiwan’s international status will be determined by a broad range of factors and competing claims. The governments of both the Kuomingtang (KMT) and the People’s Republic of China (PRC) officially consider Taiwan to be part of a unified China. The two sides only disagree about who should control this unified China and on what political principles it should be uni- fied. This concept of a unified China is essentially a modem, state- based notion. This article argues that the concepts of statehood employed in the current discourse concerning Taiwan’s future may not be consistent with objective reality, and that a reconstruction of the way such concepts are understood may be required in order to achieve meaningful dialogue and a peaceful and mutually satisfying solution to the so-called “Taiwan question.”